Elevated mercury accumulation in a peat bog of the Magellanic Moorlands, Chile (53°S): an anthropogenic signal from the Southern hemisphere - Biester, Harald; Kilian, Rolf; Franzen, Carola; Woda, Clemens; Mangini, Augusto; Schöler, Heinz Friedrich (Earth and planetary science letters, 2002)
Increasing mercury deposition rates in the Northern Hemisphere recorded in natural archives such as peat bogs or lake sediments have been documented in numerous studies. However, data on atmospheric Hg deposition in the Southern Hemisphere dating back to pre-industrial times are rare. Here, we provide a continuous record of atmospheric Hg deposition in the Southern Hemisphere recorded by an ombrotrophic peat bog of the Magellanic Moorlands, Chile (53°S), extending back 3000 yr. Pre-industrial mercury accumulation rates range between 2.5 and 3.9 μg/m2/yr. In the past 100 yr, Hg accumulation rates increased 18-fold from about 3 μg/m2/yr to a maximum of 62.5 μg/m2/yr. If Hg accumulation rates were normalized to peat accumulation rates, maximum rates were 7.9 μg/m2/yr, which is only 2.5 times the pre-industrial rates. Thus, Hg accumulation rates normalized to peat accumulation rates are more comparable to the three-fold net increase in atmospheric Hg concentrations estimated for the same period. We suggest that the increase in Hg accumulation rates in the Magellanic Moorlands within the past 100 yr is at least partly attributed to global dispersion of Hg derived from anthropogenic sources in the Northern Hemisphere. The finding that no increase of atmospheric deposition of Pb could be observed in the bog indicates the extraordinary long-range transport and ubiquitous dispersion of anthropogenic derived gaseous Hg compared to other metals.
Gesehen am 24.10.2017